"Factors Influencing the Effectiveness of Interventions to Reduce Racial and Ethnic Disparities in Health care" - Jones, Rhys Griffith (2009)
Reducing racial and ethnic disparities in health care has become an important policy goal in the United States and other countries, but evidence to inform interventions to address disparities is limited. The objective of this study was to identify important dimensions of interventions to reduce health care disparities. We used qualitative research methods to examine interventions aimed at improving diabetes and/or cardiovascular care for patients from racial and ethnic minority groups within five health care organizations. We interviewed 36 key informants and conducted a thematic analysis to identify important features of these interventions. Key elements of interventions included two contextual factors (external accountability and alignment of incentives to reduce disparities) and four factors related to the organization or intervention itself (organizational commitment, population health focus, use of data to inform solutions, and a comprehensive approach to quality). Consideration of these elements could improve the design, implementation, and evaluation of future interventions to address racial and ethnic disparities in health care.